KEBIJAKAN PENAL DAN PENANGGULANGAN TINDAK PIDANA KEKERASAN DALAM RUMAH TANGGA - Eleanora, Fransiska Novita; Siregar, Rachmat Kurniawan (LPPM Universitas Bina Bangsa, 2023)
Penal policy is an effort in overcoming crime which is usually given with sanctions or punishment to the perpetrator so that the perpetrator realizes his mistake and the crime he has committed, but in fact it is often the reluctance of the victim to report the occurrence of the crime because it is considered a personal matter and can be resolved amicably and did not report the perpetrator. The perpetrator is reported if it results in and has an impact on injuries or violence experienced by the victim so that the perpetrator must be held accountable for his actions, and given sanctions or punishments commensurate with his actions so that there is a deterrent effect for the perpetrators. While the purpose of this study is to find out how the penal policy in overcoming domestic violence. The method used is normative juridical research, namely by reviewing literature, legislation, principles, theories to answer problems. The penal policy in overcoming domestic violence is to expand the evidence that is not only based on the victim reporting but can also be expanded with other evidence, namely the statements of other witnesses so that they can report perpetrators of violence to be held accountable